Edible Mushrooms: A Green Biotechnology and Great Nutritional Value for Improving Human Health - Abdel-Aziz, Shadia M.; Hamid, Hoda A.; Fadel, M. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
In recent years, great emergence of environmental issues such as “green biotechnology” or “white biotechnology” (in EUR) is developed. Green biotechnology can be regarded as application of microorganisms or their metabolites in food, medicine, and pharmaceutical fields. Edible mushroom is an ideal food due to the fairly high content of proteins include amino acids which are essential to human health and nutrition. Mushroom fungus is easily digested, free of cholesterol, and provides a source of dietary fiber. Fungal proteins compete successfully with animal protein foods and are healthy alternative to meat. Many studies have found that some species of mushrooms are having therapeutic properties such as antioxidant, antimicrobial, anticancer, cholesterol lowering and immuno-stimulatory effects. Consumption of mushroom-rich foods is associated with a reduced risk of cardiovascular diseases, and certain types of cancer. Mushrooms have nutraceutical properties such as prevention or treatment of Parkinson, Alzheimer, hypertension, and high risk of stroke. However, some of wild mushroom are considered to be poisonous and there has been some concern about the concentration of metals such as arsenic, cadmium, copper and lead in wild fungi. Consumption of wild fungi in normal quantities is, however, did not pose any significant health risk.